Bacillus cereus isolates on the growth and nitrogen content in banana (Musa AAA) - Ortega-Bonilla, Rodya M. (2022)
Introduction. The plant growth-promoting rhizobacteria (PGPR) could be used as an alternative source to the use of conventional nitrogen fertilizers in banana (Musa AAA) cultivation. It is necessary to search for bacteria adapted to Costa Rican soil conditions and banana cultivation. Objective. To evaluate the effect of the inoculation of four Bacillus cereus isolates on the growth and nitrogen (N) content of banana seedlings under greenhouse conditions. Materials and methods. Two simultaneous experiments were carried out between April and September 2020 at the Corporacion Bananera Nacional (CORBANA) Research Center, La Rita, Limon, Costa Rica. Four isolates of B. cereus were inoculated into banana plants that were fertilized with four doses of nitrogen weekly. The design consisted of divided plots, where the main plot consisted of four levels of N: 0, 33, 66, 100 % of the dose; and the small plot consisted of the bacterial isolates and the control. The variables measured were plant height, chlorophyll content, leaf area of the third leaf, fresh and dry weight of roots, corm, pseudostem, and leaves, as well as the nitrogen content in each organ. Results. In experiment 1: the plants inoculated with the SER-23 isolate presented the highest total dry weight. In experiment 2: the highest total dry weight was observed in seedlings inoculated with the BF-98 isolate. The application of SER-23 and BF-98 bacteria significantly increased the nitrogen content in all the organs evaluated. Conclusions. The inoculation of Bacillus cereus isolates SER-23 and BF-98 stimulated the increase in biomass and nitrogen content in banana plants, this increase depended on the nitrogen availability and soil type.